Analisis Perangkat Pembelajaran IPA Berbasis Hots Kelas Tinggi di Sekolah Dasar - Diana Endah Handayani; Sari Khusnul Khuluq; Suyitno Suyitno (Peneliti.net, 2020)
This study aims to determine how the results of the analysis of HOTS-based learning tools in the form of making and implementing HOTS-based RPP and LKPD learning tools in high-grade science subjects in the odd semester SDN Bugangan 03 Semarang.This type of research is qualitative research, using the method of observation, interviews and documentation. The subjects of this study were the fourth grade teachers of SD Negeri Bugangan 03 Semarang.The results showed that in making and implementing learning tools in the form of lesson plans, the teacher was guided by Permendikbud No. 22 of 2016 concerning process standards and had directed students to HOTS with a focus on science subjects. However, the components of the Competency Achievement Indicators for teachers have not used the KKO level which is included in the HOTS level. In the LKPD a number of 12 LKPDs have directed students to the scientific approach in the form of 5M activities and 3 LKPDs have not yet referred to the scientific approach.It can be concluded that the teacher has tried to make and implement HOTS-based lesson plans even though the GPA component has not used KKO which refers to HOTS. A total of 12 LKPDs in science subjects have directed students to the scientific approach, namely 5M activities.